Multivariate Analysis of Heavy Metal Contamination in Soil of Baiyangdian Wetland in China - Su, Liya; Liu, Jingling (Journal of Environmental Accounting and Management, 2026)
Soil pollution has become an important environmental issue due to changes in the land use pattern over the last few decades. However, up to now, except Cd and Pb, little attention was paid on more heavy metals in Baiyangdian soil. This article applied multivariate statistical techniques with element concentration analysis and correlation analysis for source identification of heavy metals in the soil of Baiyangdian. The application of multivariate statistical techniques combined with element concentration analysis and correlation analysis has been proved to be an effective tool for source identification of heavy metals in Baiyangdian soil. Firstly, based on the comparison of heavy metals concentrations of soil with background values of Chinese soils, the examined elements were classified into two main groups: natural and anthropogenic sources. Then principal component analysis and cluster analysis, coupled with correlation analysis, were used to gain additional insight into the origins of different elements in soil. Three main sources for these studied elements, as well as some subdivided sources, were therefore identified. Hg, Pb and As are attributed to commercial and domestic sources; Cd and Cu are mainly derived from industrial sources and Cr and Zn associated with traffic sources.